Clinical InvestigationsOriginal articlePatterns of care study for brachytherapy: results of the questionnaire for the years 2002 and 2007 in The Netherlands - Venselaar, Jack L.M.; Slotman, Ben J.; Guedea, Ferran; Ventura, Montse; Londres, Bradley; Francois, Guy (Journal of Contemporary Brachytherapy, 2010)
Purpose : The goal of the ESTRO Patterns of Care study for Brachytherapy in Europe (PCBE) 2002 was to develop an aid to analyse brachytherapy practices. A 2nd version of the PCB questionnaire was created for 2007. Data over 2007 were collected at the radiotherapy institutions in The Netherlands and compared with those from 2002. The aim of this study is to describe national brachytherapy practices, to demonstrate trends, and to provide data for rational health care planning. Material and methods : Data were collected using a web-based questionnaire. For each centre, a local coordinator, responsible for coordinating the questionnaires and support of the further analysis was assigned. Data from the national cancer incidence registry was used for comparison with the data from the 21 Dutch departments. Results : There was a decrease in low-dose rate equipment in parallel to an increase in both pulsed-dose rate and high-dose rate equipment. The use of 3D CT and MR based imaging techniques showed a slow rise. The most common clinical procedures were for prostate, gynaecological, and oesophageal tumours. A large increase (146%) in permanent implant prostate applications using 125I seeds was observed. The numbers of oesophageal and gynaecological treatments remained stable. There is concern on the low numbers of cases treated in some institutions for a few complex treatment sites. For head and neck, anal canal, paediatrics, bladder and eye interventions it ranged from 3-20 patients per year per institution. Conclusions : The increase in number of patient treated with brachytherapy is in accordance with the increases in cancer incidence. The percentage of all radiotherapy patients treated with brachytherapy (approximately 5%) remained stable. The survey identified certain trends in resources and techniques, as well as areas of expected improvement and possible gain in clinical outcome. Data reported from this survey can be used for further planning of resources, facilities and concentration of a low-volume specialised and complex treatments.